Performansi Mengajar Guru Pendidikan Agama Islam Sekolah Dasar di Kecamatan Dewantara Kabupaten Aceh Utara - Marlina, Marlina; Nurmala, Nurmala (Jurnal Seumubeuet, 2022)
Teacher performance in teaching is one of the characteristics that need to be ideally implemented in classroom learning. This is an important factor to contribute in improving student academic achievement in elementary school. This thesis tried to examine the teacher performance in classroom management, lesson delivery, and evaluating skills in elementary schools in Islamic studies education subject in Dewantara sub-district, Aceh Utara district. The study was a field study with qualitative approach. It was conducted in several public elementary schools: SDN 1, SDN 3, SDN 12, and SDN 15, in Dewantara sub-district, Aceh Utara district. The techniques of data collection included interview, observation, and documentation. The data were then analyzed by data reduction, data display, and data verification. The results of the study showed that the performance in classroom management has been good. The teachers could control the classroom well, adapt with the students, and deliver the lesson properly. Thus, the learning process was run effectively. Further, the teachers have already put their maximum efforts in delivering the lesson, made necessary adjustments in their classroom, as well as asked the students if they had any problems during class. The evaluation was done by giving the students multiple choice test, essay test, oral test, and homework. Monthly exams were also given to the students as part of the classroom evaluation.